Student Teams Achievement Division (STAD) Toward Students’ Ability In Essay Writing At SMP Methodist 7 Medan - Irman Toni Silalahi; Yessy Octavianna; Kammer Sipayung (Sean Institute, 2024)
Student Team Achievement Division (STAD) is a social-based learning that teaches students social interaction in small groups. The purpose of this study is to find out whether the teaching method of the STAD model affects the ability of the students to write the essay at Methodist 7 Field High School students in grade IX. The type of quasi-experimental research used in this study, with the design of one pre-test group and one post-test Group. The focus of this research is the student's ability to write before and after using the STAD Model; the subject of the study is a student of the 9th grade at Methodist 7 Field High School, which consists of 17 students. The method of data collection is a written test. The results of this study show that the teaching method of the STAD model affects the ability of X-grade students to write essays in the 7th Methodist Field. The data of the study had a normal distribution of 6.31. The results of data analysis with the test-t showed that T-count = 6.31 with a degree of significance α = 5% and dk (n-1) = (17-1)=16, so T-table = 1.33. It means HO is rejected and Ha is accepted.